2016
DOI: 10.4238/gmr15048973
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype evolution in the genus Jacaranda Juss. (Jacarandeae, Bignoniaceae): chromosome numbers and heterochromatin

Abstract: ABSTRACT. Most taxa in the Bignoniaceae have 2n = 40, but the basal clade Jacarandeae has 2n = 36, suggesting that x = 18 is the ancestral basic number for the family. Variations in heterochromatin band patterns in genera that are numerically stable, such as Jacaranda, could facilitate our understanding of the chromosomal and karyotypic evolution of the family. We characterized heterochromatin distributions in six Jacaranda species using chromomycin A3 (CMA) and 4'6-diamidino-2-phenylindole (DAPI). All of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Although Gentry and Morawetz (1992) recognized J. cuspidifolia as closely related to (but allopatric with) J. brasiliana (Lamark) Persoon, the similarity between the former species and J. mimosifolia has also been stressed (Lorenzi 2002). Considering the karyotype stability of the genus (Cordeiro et al 2016), the cross-compatibility of J. cuspidifolia and J. mimosifolia demonstrated by Miyajima et al (2013) and by the present study also indicate a low level of incongruity operating between these species, which seems to point to their recent evolutionary divergence.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Although Gentry and Morawetz (1992) recognized J. cuspidifolia as closely related to (but allopatric with) J. brasiliana (Lamark) Persoon, the similarity between the former species and J. mimosifolia has also been stressed (Lorenzi 2002). Considering the karyotype stability of the genus (Cordeiro et al 2016), the cross-compatibility of J. cuspidifolia and J. mimosifolia demonstrated by Miyajima et al (2013) and by the present study also indicate a low level of incongruity operating between these species, which seems to point to their recent evolutionary divergence.…”
Section: Discussionsupporting
confidence: 65%
“…Jacaranda is one of the largest genera of the family Bignoniaceae (Gentry and Morawetz 1992). The genus exhibits a notable karyotype stability -all the analyzed species (41% of the genus, including both species in this study) have 2n = 36 (Cordeiro et al 2016) -, and a conservative breeding system -except for the reports on self-compatibility (SC) in J. mimosifolia (Battacharjee and Sareen 1991) and J. oxyphylla (Yanagizawa and Maimoni-Rodella 2007), all the other studied species (18% of the genus) have been reported to be strongly self-sterile, most of them with indications of late-acting self-incompatibility (LSI) (Vieira et al 1992, Bittencourt and Semir 2006, Yanagizawa and Maimoni-Rodella 2007, Guimarães et al 2008, Maués et al 2008, Milet-Pinheiro and Schlindwein 2009, Sampaio 2010. Species of Jacarandeae are melittophilous, and this is the most common pollination syndrome in Bignoniaceae (Gentry 1980).…”
Section: Introductionmentioning
confidence: 76%
“…Those variations can reflect the results of various cytological phenomena, especially satellite DNA amplification (Guerra 2000;Silva et al 2010;Ribeiro et al 2016). Differences in heterochromatic banding patterns are quite useful for cytotaxonomic characterizations of plant species, especially among those having karyotypes formed by morphologically similar chromosomes that are numerically stable (Guerra 2000;Scaldaferro et al 2012;Cordeiro et al 2016). The observed differences in the CMA/ DAPI banding patterns in Senna ratified the effectiveness of that technique for facilitating karyological differentiation of its species.…”
Section: Discussionmentioning
confidence: 96%
“…Those authors reported the occurrence of two chromosome pairs with terminal or subterminal CMA + /DAPI -bands in most of the species analyzed, with the exception of a population of Senna obtusifolia (which demonstrated two chromosome pairs with terminal DAPI + /CMA -bands). Studies of heterochromatin patterns can be important tools for understanding the taxonomic relationships between different plant species, especially those that are morphologically very similar (Pessoa et al 2014;Almeida et al 2016;Cordeiro et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Both fluorochromes are used with the same specimens, resulting in differential coloring patterns: CMA stains GC-rich regions, whereas DAPI stains only AT-rich regions (Guerra 2000). This type of analysis has been used to distinguish the cytotypes of species belonging to different hierarchical levels, such as families (Cordeiro et al 2017), species of the same genus (Almeida et al 2007, 2016, Cordeiro et al 2016b, and even cultivars and populations of the same species (Dematteis et al 2006, Romero-da Cruz et al 2015, Begum and Alam 2016.…”
Section: Introductionmentioning
confidence: 99%